Redescription of the serranid perchlet Chelidoperca pleurospilus (Günther, 1880) - Matsunuma, Mizuki; Tashiro, Fumihito (Zootaxa, 2020)
Chelidoperca pleurospilus (Günther, 1880) (Perciformes: Serranidae) is redescribed on the basis of the lectotype (designated herein) and 69 non-type specimens from the eastern Indian and western Pacific oceans, ranging from the Andaman Sea east to New Caledonia, and northwestern Australia north to Japan. Literature records of the species from the Red Sea and Madagascar are considered applicable to Chelidoperca occipitalis Kotthaus 1973. Chelidoperca pleurospilus is characterized by the following combination of characters: pectoral-fin rays 14–16 (modally 15); pored lateral-line scales 40–43 (43); scale rows in longitudinal series 42–47 (44); scale rows between lateral line and base of 6th dorsal-fin spine 4 (3 full-sized scales plus 1 half-sized); interorbital scales reaching mid-orbit level, not extending beyond anterior margin of orbit; scales on lower jaw ventral surface restricted to angular, not extending anteriorly onto dentary; posterior tip of upper caudal-fin lobe slightly elongate with rounded or pointed contour, that of lower lobe not elongate, with rounded or truncate contour; longitudinal row of ca. 5 dark, laterally elongate blotches (more-or-less continuous in small specimens <60 mm SL) along mid-body from behind head to caudal-fin base. The species is compared with its congeners, and morphological changes with growth in the former discussed in detail.